La honte - Ernaux, Annie (Gallimard, 1997)
J'ai toujours eu envie d'écrire des livres dont il me soit ensuite impossible de parler, qui rendent le regard d'autrui insoutenable. Mais quelle honte pourrait m'apporter l'écriture d'un livre qui soit à la hauteur de ce que j'ai éprouvé dans ma douzième année.
Section: 132 pages ; 19 cm
Keywords: 1900-1999; 1940-1949; approches et analyses; classisme; cours; discipline; discours dominant; europe; france; inégalités; lit301N; littérature; premier cycle; périodes historiques; régions géographiques; systèmes d'oppressions; thématiques; écriture des femmes*

Cross-purposes: Lesbians, feminists, and the limits of alliance - Heller, Dana Alice (Indiana University Press, 1997)
Une collection de quinze essais interdisciplinaires examinant l'histoire, la situation actuelle et l'évolution des alliances lesbiennes avec les féministes américaines. Les contributeurs explorent la signification sociale et esthétique des termes « lesbienne » et « féministe » dans le but de les réformer et de les renforcer.
Keywords: amériques; approches et analyses; discours dominant; hétérosexisme; lesbianisme; personnes lesbiennes; régions géographiques; systèmes d'oppressions; états-unis

Same sex, different cultures: exploring gay and lesbian lives - Herdt, Gilbert H. (Westview Press, 1997)
Because homoerotic relations can be found in so many cultures, Gilbert Herdt argues that we should think of these relations as part of the human condition. This new cross-cultural study of gays, lesbians, and bisexuals around the world, Same Sex, Different Cultures provides a unique perspective on maturing and living within societies, both historical and contemporary, that not only acknowledge but also incorporate same-gender desires and relations. Examining what it means to organize "sex" in a society that lacks a category for "sex", or to love someone of the same gender when society does not have a "homosexual" or "gay/lesbian" role, Herdt provides provocative new insights in our understanding of gay and lesbians lives. Accurate in both its scientific conceptions and wealth of cultural and historical material, examples range from the ancient Greeks and feudal China and Japan to the developing countries of Africa, India, Mexico, Brazil, and Thailand, from a New Guinea society to contemporary U.S. culture, including Native Americans. For all of these peoples, homoerotic relations emerge as part of culture and not separate from history or society. In many of these groups, loving or engaging in sexual relations is found to be the very basis of the local cultural theory of "human nature" and the mythological basis for the cosmos and the creation of society. The mistake of modern Western culture, Gilbert contends, is to continue the legalization of prejudice against lesbians and gays. In this light, the book addresses the issue of "universal" versus particular practices and reveals positive role models that embrace all aspects of human sexuality. Finally, it offers knowledge of the existence of persons who have loved and have been intimate sexually and romantically with the same gender in other lands through divergent cultural practices and social roles. The most important lesson to learn from this cross-cultural and historical study of homosexuality is that there is room for many at the table of humankind.
Keywords: LGBTQIA2+; approche interculturelle; approches et analyses; cours; discipline; discours dominant; histoire; histoire et politique; hétérosexisme; patriarcat; premier cycle; sciences humaines; soc2014; sociologie; système colonial; systèmes d'oppressions; thématiques

Dangerous liaisons: gender, nation and postcolonial perspectives - McClintock, Anne; Shohat, Ella; Mufti, Aamir Rashid (Minnesota University Press, 1997)
This collection addresses the issues raised by the postcolonial condition, considering nationhood, history, gender and identity from an interdisciplinary perspective.
Contenu: Introduction / Aamir Mufti and Ella Shohat – pt. I. Contesting Nations. 1. Zionism from the Standpoint of Its Victims / Edward W. Said. 2. Sephardim in Israel: Zionism from the Standpoint of Its Jewish Victims / Ella Shohat. 3. Of Balkans and Bantustans: Ethnic Cleansing and the Crisis in National Legitimation / Rob Nixon. 4. "No Longer in a Future Heaven": Gender, Race, and Nationalism / Anne McClintock. 5. Currying Favor: The Politics of British Educational and Cultural Policy in India, 1813-54 / Gauri Viswanathan. 6. The Nation as Imagined Community / Jean Franco – pt. II. Multiculturalism and Diasporic Identities. 7. On the Question of a Theory of (Third) World Literature / Madhava Prasad. 8. Caliban Speaks Five Hundred Years Later / Roberto Fernandez Retamar. 9. The Local and the Global: Globalization and Ethnicity / Stuart Hall. 10. Multiculturalism and the Neoconservatives / Robert Stam. 11. Shuckin' Off the African-American Native Other: What's "Po-Mo" Got to Do with It? / Wahneema Lubiano. 12. Identity, Meaning, and the African-American / Michael Hanchard. 13. Just Looking for Trouble: Robert Mapplethorpe and Fantasies of Race / Kobena Mercer – pt. III. Gender and the Politics of Race. 14. Under Western Eyes: Feminist Scholarship and Colonial Discourses / Chandra Talpade Mohanty. 15. Traddutora, Traditora: A Paradigmatic Figure of Chicana Feminism / Norma Alarcon. 16. American Indian Women: At the Center of Indigenous Resistance in Contemporary North America / M. Annette Jaimes and Theresa Halsey. 17. "On the Threshold of Woman's Era": Lynching, Empire, and Sexuality in Black Feminist Theory / Hazel V. Carby. 18. Making Empire Respectable: The Politics of Race and Sexual Morality in Twentieth-Century Colonial Cultures / Ann Laura Stoler. 19. Age, Race, Class, and Sex: Women Redefining Difference / Audre Lorde. 20. Gender Is Burning: Questions of Appropriation and Subversion / Judith Butler. 21. Sisterhood: Political Solidarity between Women / Bell Hooks – pt. IV. Postcolonial Theory. 22. Not You/Like You: Postcolonial Women and the Interlocking Questions of Identity and Difference / Trinh T. Minh-ha. 23. Is the "Post-" in "Postcolonial" the "Post-" in "Postmodern"? / Kwame Anthony Appiah. 24. The World and the Home / Homi K. Bhabha. 25. Reading Africa through Foucault: V.Y. Mudimbe's Reaffirmation of the Subject / Manthia Diawara. 26. Teaching for the Times / Gayatri Chakravorty Spivak. 27. Postcolonial Criticism and Indian Historiography / Gyan Prakash. 28. The Postcolonial Aura: Third World Criticism in the Age of Global Capitalism / Arif Dirlik. Le texte "Age, Race, Class, and Sex : Women Redefining Difference" de Audre Lorde a été donné en lecture au cours LIT4700.
Keywords: LGBTQIA2+; approches et analyses; arts; cours; discipline; discours dominant; féminisme décolonial; histoire et politique; identités LGBTQIA2+; intersectionnalité; inégalités; lit4700; militance; poésie; premier cycle; queer; racisme; sexisme; systèmes d'oppressions; thématiques; études culturelles; études littéraires

Des mots, des pratiques et des risques : la gestion différenciée de la parole et de la prévention du VIH chez des hommes à comportements bisexuels en France - Mendès-Leite, Rommel; Deschamps, Catherine (Sociologie et sociétés, 1997)
Cet article présente une partie des résultats de deux recherches socio-anthropologiques réalisées en France auprès d'hommes ayant des rapports sexuels avec des hommes et des femmes, indépendamment de leur identité socio-sexuelle. Les analyses portent d'abord sur les perceptions différenciées de la sexualité et sur ses conséquences en matière de restitution du sens, et ensuite sur la gestion des comportements préventifs. Ainsi il apparat!, au travers d'une relecture des notions de " multipartenariat ", de " sexe occasionnel " ou de " fidélité ", que le principal lieu de rupture dans la gestion des risques vin est avant tout dépendant de la variable sexe des partenaires sexuels, quand bien même la compréhension de ce mécanisme ne se réduit pas à une opposition basique entre hommes et femmes.
Keywords: 1900-1999; VIH; analyse différenciée selon les sexes -ADS+; anthropologie; approches et analyses; cours; discipline; discours dominant; europe; france; his4860; histoire et politique; hétérosexisme; justice sociale; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexualité; sexualité masculine; sociologie; systèmes d'oppressions; thématiques

Les lesbiennes et le roman français 1796-1996 - Waelti-Walters, Jennifer (Nouvelles Questions Féministes, 1997)
La lesbienne telle qu'on la connaît aujourd'hui est entrée dans le roman français avec La Religieuse de Diderot (pub. 1796), et jusqu'en 1926 elle est créée et recréée presqu'exclusivement par les écrivains hommes qui modèlent leurs personnages sur Margarita de La Fille aux yeux d'or de Balzac et Mademoiselle de Maupin de Gautier, pour en faire des femmes menaçantes pour la virilité collective. A partir de 1930 les expériences littéraires lesbiennes sont prises en charge par des auteures femmes qui en explorent les secrets, les misères et les oppressions d'abord, et ensuite — à partir de l'oeuvre de Monique Wittig et de Jocelyne François — la vie quotidienne dans sa variété. Cet article est un compte rendu d'unprojet de recherche en cours — projet qui étudie un territoire littéraire jusqu'ici totalement ignoré dans l'histoire du roman.
Keywords: approches et analyses; arts; discipline; discours dominant; europe; france; histoire du roman; hétérosexisme; patriarcat; personnes lesbiennes; régions géographiques; systèmes d'oppressions; études littéraires